Food science and technology bulletin functional foods. Vol. 4 - Gibson, Glenn R. (IFIS, 2008)
Food science and technology bulletin: Functional foods is designed to meet the current-awareness needs of busy food professionals working in food science and technology.
Keywords: Functional foods.; Food industry and trade.; elektronické knihy; electronic books